A cost-effective process for recovering thorium and rare earths from radioactive residues. (1st May 2020) - Su, Jia; Xu, Ruigao; Ni, Shuainan; Li, Fujian; Sun, Xiaoqi
Abstract: Ion-adsorbed rare earth ores radioactive residues (IREORR) are low-level radioactive wastes generated by the production processes of ion-adsorbed rare earth ores (IREO). IREORR were difficult to be managed due to their radioactivity and larger volume. The wastes have caused environmental concerns. In addition, IREORR were rich in rare earth elements (REEs). The contents of REEs in IREORR were much higher than those in IREO. In this study, a separation process based on 2-(4-(2, 4, 4-trimethylpentan-2-yl) phenoxy) acetic acid (POAA) for the recoveries of REEs and radioactive element Th from IREORR leachate have been developed. The extraction mechanism of POAA for Th was indicated to be cation exchange mechanism. Unsaponified POAA revealed a better selectivity for the separation of Th from mixed REEs. The separation of Th and enrichment of REEs from IREORR leachate were achieved by liquid-liquid extraction and extraction-precipitation, showing that this process may be cost-effective used to deal with IREORR leachate for environmental concerns and resource utilizations. Graphical abstract: Image 1